A study of dual function and expression pattern of Klf4 between two different processes of differentiation and maintenance of pluripotency in spermatogonial stem cells - Sojoudi, Kiana; Azizi, Hossein; Skutella, Thomas (Andrologia, 2024)
Krüppel-like factor 4 (Klf4) is a transcription factor involved in proliferation, self-renewal, differentiation, apoptosis, and somatic cell reprogramming; thus, it has a critical role in accurate spermatogenesis. In this study, we examine the different protein localizations of Klf4 in the mouse testis and in two populations of spermatogonial stem cells (SSCs), including differentiated and undifferentiated cell types. We show that in contrast to its function during spermatogenesis in the adult testis, in vitro Klf4 is a factor in maintaining stemness in different SSC populations. Furthermore, we suggest that its functions could be age-dependent. Bioinformatics analysis in the Cytoscape platform was conducted to highlight pathways and networks of Klf4 interactions. Our results support the different functions of Klf4 dependent on the age and differentiation state of SSCs.